2014
DOI: 10.1093/nar/gku1289
|View full text |Cite
|
Sign up to set email alerts
|

A novel RNA molecular signature for activation of 2′-5′ oligoadenylate synthetase-1

Abstract: Human 2′-5′ oligoadenylate synthetase-1 (OAS1) is central in innate immune system detection of cytoplasmic double-stranded RNA (dsRNA) and promotion of host antiviral responses. However, the molecular signatures that promote OAS1 activation are currently poorly defined. We show that the 3′-end polyuridine sequence of viral and cellular RNA polymerase III non-coding transcripts is critical for their optimal activation of OAS1. Potentiation of OAS1 activity was also observed with a model dsRNA duplex containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 44 publications
3
45
0
Order By: Relevance
“…nc886 adopts two distinct structures which differ in their migration on native polyacrylamide gels and their ability to inhibit PKR: the slower migrating form ("Conformer 1") is a potent PKR inhibitor while the faster migrating form ("Conformer 2") is a weak PKR activator that acts as a pseudoinhibitor at higher concentrations in the presence of another PKR-activator such as poly(I:C) RNA. As noted earlier, we also showed that nc886 can activate OAS1 in vitro as a mixture of conformers (Vachon et al, 2015). A more recent detailed study of OAS1 activation by nc886 in vitro and in A549 cells revealed that most activity is conferred by a unique tertiary structure motif present only in the apical stem-loop of nc886 Conformer 1 (Calderon & Conn, 2018).…”
Section: F I G U R E 3 Legend On Next Pagesupporting
confidence: 85%
“…nc886 adopts two distinct structures which differ in their migration on native polyacrylamide gels and their ability to inhibit PKR: the slower migrating form ("Conformer 1") is a potent PKR inhibitor while the faster migrating form ("Conformer 2") is a weak PKR activator that acts as a pseudoinhibitor at higher concentrations in the presence of another PKR-activator such as poly(I:C) RNA. As noted earlier, we also showed that nc886 can activate OAS1 in vitro as a mixture of conformers (Vachon et al, 2015). A more recent detailed study of OAS1 activation by nc886 in vitro and in A549 cells revealed that most activity is conferred by a unique tertiary structure motif present only in the apical stem-loop of nc886 Conformer 1 (Calderon & Conn, 2018).…”
Section: F I G U R E 3 Legend On Next Pagesupporting
confidence: 85%
“…Of them, rs1051042 is the lead eQTL SNP (ie, eSNP) on the OAS1 gene, suggesting potential causality of the OAS1 gene. The OAS1 gene synthesises an antiviral enzyme and then results in viral RNA degradation39 and may inhibit virus replication, which is a common environment trigger for SLE, and affect the risk and disease activity of SLE 40 41. The A risk allele of SNP rs1335532 significantly upregulates the expression level of the CD58 gene 24.…”
Section: Discussionmentioning
confidence: 99%
“…To dissect the activity of each conformer on OAS1, we purified the individual nc886 conformers by native PAGE. An established in vitro OAS1 activation assay (27,28) was then used to measure PP i production, the by-product of 2-5A synthesis, in the presence of each nc886 conformer. nc886 conformer 1 strongly activates OAS1 ( Fig.…”
Section: Oas1 Is Potently Activated By a Single Nc886 Conformermentioning
confidence: 99%
“…Our previous work has demonstrated that nc886 RNA adopts two structurally distinct conformers, distinguished by their apical stem-loop structures, that possess opposing activi-ties in the regulation of PKR (26). We also previously reported that the mixture of nc886 conformers appeared to strongly activate OAS1 and that this activity was only modestly reduced by deletion of the 3Ј-single-stranded pyrimidine (3Ј-ssPy) motif that more significantly potentiates activity by viral noncoding RNAs (27). Here, we show that the two nc886 conformers exhibit profound differences in their capacity to activate the OAS/RNase L pathway: one nc886 conformer is a potent activator of OAS1 in vitro and in human A549 cells whereas the other conformer activates OAS1 only very weakly.…”
mentioning
confidence: 99%